SPIRITUALITAS DALAM PERILAKU ORGANISASI - Hasan Hasan (Universitas Islam Nahdlatul Ulama Jepara, 2010)
AbstractThis paper reviews spirituality which is a new subject in the study of organizational behavior. By doing a literature review, this paper discuss the concept of spirituality, development and research examples, and some previous theoretical concepts that could form the basis of theoretical study of the development of spirituality in organizational behavior. In the future, the study of spirituality can be developed further by strengthening the theoretical foundation and improve the design of empirical research methodology.Keywords: Spirituality, organizational behaviorAbstrakTulisan ini mengkaji spiritualitas yang merupakan bahasan baru dalam kajian perilaku organisasional. Dengan melakukan kajian literatur, artikel ini membahas konsep spiritualitas, perkembangan dan contoh penelitian, dan beberapa konsep teoritis sebelumnya yang dapat menjadi landasan pengembangan teoritis kajian spiritualitas dalam perilaku organisasional. Di masa yang akan datang, kajian spiritualitas dapat dikembangkan lebih lanjut dengan memperkuat landasan teoritis dan meningkatkan desain metodologi penelitian empiris.Kata Kunci: Spiritualitas, Perilaku organisasi